2017
DOI: 10.3390/polym10010003
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing and Characterization of Toughened Poly(lactic acid) (PLA) Formulations by Ternary Blends with Biopolyesters

Abstract: Ternary blends with a constant poly(lactic acid) (PLA) content (60 wt %) and varying amounts of poly(3-hydroxybutyrate) (PHB) and poly(ε-caprolactone) (PCL) were manufactured by one step melt blending process followed by injection moulding, with the main aim of improving the low intrinsic toughness of PLA. Mechanical properties were obtained from tensile and Charpy impact tests. The miscibility and morphology of the system was studied by thermal analysis and field emission scanning electron microscopy (FESEM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…J. Urquijo et al demonstrated the relevance of the elongation rate on the final elongation and, regarding the impact strength, they attributed the improvement to the small particle size of PCL-rich domains embedded in the brittle PLA-rich matrix which positively contributed to absorb energy in impact conditions. Similar findings have been reported with PLA/PCL, PHB/PCL, PLA/PBS binary blends [46,47,48,49], ternary PLA/PHB/PCL blends [50], and some poly(ester) copolymers [51]. This improved toughness is more evident in an uncompatibilzed blend containing 30 wt % bioPA1010 reaching an impact strength of 40.5 kJ·m −2 (75.3% increase).…”
Section: Resultssupporting
confidence: 84%
“…J. Urquijo et al demonstrated the relevance of the elongation rate on the final elongation and, regarding the impact strength, they attributed the improvement to the small particle size of PCL-rich domains embedded in the brittle PLA-rich matrix which positively contributed to absorb energy in impact conditions. Similar findings have been reported with PLA/PCL, PHB/PCL, PLA/PBS binary blends [46,47,48,49], ternary PLA/PHB/PCL blends [50], and some poly(ester) copolymers [51]. This improved toughness is more evident in an uncompatibilzed blend containing 30 wt % bioPA1010 reaching an impact strength of 40.5 kJ·m −2 (75.3% increase).…”
Section: Resultssupporting
confidence: 84%
“…The second one was observed in the 400−510 ºC range, which can be ascribed to the chain-scission process of bio-HDPE. In this sense, Garcia-Campo et al 58 has recently analyzed the thermal degradation of PLA, showing that the thermal decomposition of the biopolyester occurs in one single step, in the 300−400 ºC range, with T5% and Tdeg values of 328.5 °C and 368.5 °C, respectively.…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…In recent years, biodegradable polymers represent an alternative to replace petroleum-based resins due to increasing environmental concerns [1,2,3]. Among the different biodegradable materials, poly (lactic acid) (PLA) is widely used for commercial products [4].…”
Section: Introductionmentioning
confidence: 99%